Anchorage strength development of headed bars in HSRC external beam-column joints considering side-face blowout failure under monotonic loading. (15th July 2021) - Chiu, Chien-Kuo; Lays, David Pratama; Ricky,; Krasna, Wiku Adhiwicaksana
Highlights: Specimens and FEA are used to investigate the SBF of headed bars in HSRC joints. Critical parameters to avoid the SBF mode of headed bars in HSRC joints are proposed. Engineering graphs for designing headed bars in HSRC joints are provided. Abstract: As the use of headed bars in reinforced concrete (RC) beam or column members has increased in recent years, preventing their unexpected failure modes has become an increasingly important part of their design. Headed bars that are embedded in concrete under tensile loading have six potential failure mechanisms, one of the critical failure modes is side-face blowout failure (SBF). Since the selected existing models of anchorage strength related to SBF for a headed bar were developed based on specimens with normal-strength reinforced concrete, they should be experimentally verified to investigate their application to high-strength reinforced concrete (HSRC) members. Therefore, in this work, HSRC external beam-column joints are designed based on the results of a parametric study and ACI 318-14. Based on the experiment (12 full-scale specimens) and results of simulations using finite-element analysis (FEA), when the diameter of a headed bar that is embedded in HSRC external beam-column joints is ≤ 35 mm, its minimal clear concrete cover could be reduced to be the diameter multiplied by 1.5. Additionally, with the diameter or yield strength increasing, this work also provides the engineering graphs for designing headed bars in HSRC external beam-column joints to prevent SBF before the bar yielding.